Reservation and Development of Vietnamese Dong Ho Folk Painting - Bach, Thi Ngoc Trang; Kim, Young-soon (International Journal of Social Sciences and Management, 2015)
Dong Ho folk painting is a line of Vietnamese folk painting originating in Dong Ho village (Song H? commune, Thu?n Thành District, B?c Ninh Province). It is a culture heritage of Vietnam; so the preservation and development have been requisite. In this study, we endeavored to discover the meanings and values of Dong Ho folk painting; to find out the reasons why Dong Ho folk painting fell into oblivion and recent status of of Dong Ho folk painting village; then to propose some solutions to restore and develop it. Furthermore, in the trend of globalization, preservation and development of Dong Ho folk painting is the best methods to partly diffuse Vietnam’s traditional culture with its diversification. DOI: http://dx.doi.org/10.3126/ijssm.v2i2.12333 Int. J. Soc. Sci. Manage. Vol-2, issue-2: 157-164